Silver Nanoparticles Synthesized from Abies alba and Pinus sylvestris Bark Extracts: Characterization, Antioxidant, Cytotoxic, and Antibacterial Effects - Irina Macovei; Simon Vlad Luca; Krystyna Skalicka-Woźniak; Cristina Elena Horhogea; Cristina Mihaela Rimbu; Liviu Sacarescu; Gabriela Vochita; Daniela Gherghel; Bianca Laura Ivanescu; Alina Diana Panainte; Constantin Nechita; Andreia Corciova; et al. (MDPI AG, 2023)
In recent years, phytofunctionalized AgNPs have attracted great interest due to their remarkable biological activities. In the present study, AgNPs were synthesized using Abies alba and Pinus sylvestris bark extracts. The chemical profile of these bark extracts was analyzed by LC-HRMS/MS. As a first step, the synthesis parameters (pH, AgNO3 concentration, ratio of bark extract and AgNO3, temperature, and reaction time) were optimized. The synthesized AgNPs were characterized by ATR-FTIR spectroscopy, DLS, SEM, EDX, and TEM. Their antioxidant, cytotoxic, and antibacterial properties were evaluated by the DPPH, ABTS, MTT, and broth microdilution assays, respectively. Abies alba and Pinus sylvestris bark extract-derived AgNPs were well-dispersed, spherical, small (average particle size of 9.92 and 24.49 nm, respectively), stable (zeta potential values of −10.9 and −10.8 mV, respectively), and cytotoxic to A-375 human malignant melanoma cells (IC50 = 2.40 ± 0.21 and 6.02 ± 0.61 μg/mL, respectively). The phytosynthesized AgNPs also showed antioxidant and antibacterial effects.